1964
DOI: 10.1055/s-0038-1654814
|View full text |Cite
|
Sign up to set email alerts
|

Hypercephalinemia and Experimental Venous Thrombosis in the Rat

Abstract: Summary and ConclusionNine, 18 and 36 mg per kg body weight of a crude cephalin prepared from rat brain were suspended in saline and injected intraperitoneally in rats. The influence on coagulation, platelet adhesiveness, antifibrinolytic activity and incidence of experimental venous thrombosis was studied.The following observations were made:1. The recalcification time of plasma was shortened maximally one hour after the injection, with gradual return to normal values. Normal recalcification time was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1964
1964
1972
1972

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…(1963) also found increased thrombus formation in the extracorporeal shunt of pigs fed diets supplemented by egg yolk or lard. Bergentz et al (1961) found that cream and cheese diets increased thrombus formation in ligated veins of rabbits and rats, and recently it has been shown that the incidence of thrombosis in injured veins was increased in rats fed the same fat diets as in the present study (Nordoy 1964).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…(1963) also found increased thrombus formation in the extracorporeal shunt of pigs fed diets supplemented by egg yolk or lard. Bergentz et al (1961) found that cream and cheese diets increased thrombus formation in ligated veins of rabbits and rats, and recently it has been shown that the incidence of thrombosis in injured veins was increased in rats fed the same fat diets as in the present study (Nordoy 1964).…”
Section: Discussionsupporting
confidence: 75%
“…(1963) induced thrombosis by mobilization of fatty acids by injection of ACTH or pituitary extract in rabbits. Clot promoting phospholipids have also been shown to increase thrombus formation in injured veins as well as in the extracorporeal shunt (Nordoy 1964, Mustard 1964. Thus, the changes induced in plasma lipids, both by diet and by the means described above, are associated with a thrombotic condition.…”
Section: Discussionmentioning
confidence: 99%